Effect of separation distance between on-site sanitation systems and groundwater sources on faecal contamination: A systematic review and meta-analysis - Gita L. Putri; Elzavira Felaza; Cindy R. Priadi; Juliet Willetts; Tim Foster (Water Research, 2026)

Groundwater-based water services as complex socio-hydrogeological systems: insights from Vietnam’s Mekong Delta - Naomi Carrard; Diana Gonzalez; Jess MacArthur; Nguyen Anh Minh; Nguyen Dinh Giang Nam; David Rodgers; Tim Foster (Hydrogeology Journal, 2026)
Groundwater systems are critical to global water security, yet the complex interactions between household coping strategies, resource sustainability, and climate change remain difficult to govern. This study applies qualitative systems mapping to characterise socio-hydrogeological dynamics in Vietnam’s Mekong Delta, a region currently facing intensifying saline intrusion and rapid land-use change. Drawing on a household survey ( n = 404) and in-depth interviews ( n = 25) in Sóc Trăng and Trà Vinh provinces, three critical system interactions were identified: (1) climate variability and household adaptation intensify groundwater system pressures, (2) policy-practice gaps undermine effective management of a multisource water system, and (3) social vulnerability and water stress constrain resilience. Together, these interactions illustrate how household behaviours, institutional arrangements, and resource conditions are interconnected in ways that shape system behaviour. These findings advance socio-hydrogeological frameworks by using systems mapping to make visible the relationships and interactions that influence groundwater-based water services. The research offers evidence for policymakers, suggesting that inclusive, climate-resilient service delivery depends on integrating actual household water behaviours into planning and groundwater governance, moving beyond a singular focus on piped supply.

Assessing disease burden from pathogen release through untreated hospital wastewater to neighboring communities in Dhaka city - Nuhu Amin; Tim Foster; Jay Falletta; Juliet Willetts (International Journal of Hygiene and Environmental Health, 2026)

Using systems thinking for learning about possible improvements to water and sanitation configurations for diverse urban needs in Siem Reap, Cambodia - Simon Ross; Simon Fane; Tim Foster; Sunday Yim (Environmental Development, 2026)

Cumulative effects analysis to inform public land management in the United States: key characteristics and legal challenges - Tait K. Rutherford; Tim O. Hammond; Alison C. Foster; Megan A. Gilbert; Travis S. Haby; Richard J. Lehrter; Jennifer K. Meineke; Ella M. Samuel; Sarah K. Carter (Environmental Impact Assessment Review, 2026)

On-site sanitation systems and fecal contamination in shallow groundwater in urban Indonesia: assessing influence of distance and rainfall variables - Gita L. Putri; Akna M. Ilmi; Rahayu Handayani; Dadang Iskandar; Cindy R. Priadi; Juliet Willetts; Tim Foster (Water Research, 2025)

Residential end-use water demand analysis for a heterogeneous urban water and sanitation configuration in Siem Reap, Cambodia - Simon Ross; Simon Fane; Tim Foster; Sunday Yim (Journal of Cleaner Production, 2025)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

The influence of mucilage-rich flours from diverse Australian Plantago species on the pasting, storage, and gluten-free breadmaking properties of rice flour - James M. Cowley; Yi Ren; Lucija Štrkalj; Tim J. Foster; Rachel A. Burton (Food Hydrocolloids, 2025)

Current state of plant conservation translocations across Europe: motivations, challenges and outcomes - Sandrine Godefroid; Sam Lacquaye; Andreas Ensslin; Sarah Dalrymple; Thomas Abeli; Hannah Branwood; Inmaculada Ferrando Pardo; P. Pablo Ferrer Gallego; Elke Zippel; Luísa Gouveia; Carlos Alberto Lobo; Francisco Fernandes; et al. (Biodiversity and Conservation, 2025)

Hospital wastewater (HWW) treatment in low- and middle-income countries: A systematic review of microbial treatment efficacy - Nuhu Amin; Tim Foster; Nafeya Tabassum Shimki; Juliet Willetts (Science of The Total Environment, 2024)

Policy and regulatory context for self-supplied drinking water services in two cities in Indonesia: Priorities for managing risks - Cindy Rianti Priadi; Evelyn Suleeman; Linda Darmajanti; Gita Lestari Putri; Franziska Genter; Tim Foster; Juliet Willetts (Environmental Development, 2024)

Organophosphate ester flame retardants and plasticizers in house dust and mental health outcomes among Canadian mothers: A nested prospective cohort study in CHILD - Stephanie A. Foster; Molly L. Kile; Perry Hystad; Miriam L. Diamond; Liisa M. Jantunen; Piush J. Mandhane; Theo J. Moraes; Garthika Navaranjan; James A. Scott; Elinor Simons; Padmaja Subbarao; Tim K. Takaro; et al. (Environmental Research, 2024)

Carbon emissions from refrigeration used in the UK food industry - Foster Alan; Brown Tim; Evans Judith (International Journal of Refrigeration, 2023)

Developing an ocean best practice: A case study of marine sampling practices from Australia - Rachel Przeslawski; Neville Barrett; Andrew Carroll; Scott Foster; Brooke Gibbons; Alan Jordan; Jacquomo Monk; Tim Langlois; Ana Lara-Lopez; Jay Pearlman; Kim Picard; Joni Pini-Fitzsimmons; et al. (Frontiers in Marine Science, 2023)
Since 2012, there has been a surge in the numbers of marine science publications that use the term ‘best practice’, yet the term is not often defined, nor is the process behind the best practice development described. Importantly a ‘best practice’ is more than a documented practice that an individual or institution uses and considers good. This article describes a rigorous process to develop an ocean best practice using examples from a case study from Australia in which a suite of nine standard operating procedures were released in 2018 and have since become national best practices. The process to develop a best practice includes three phases 1) scope and recruit, 2) develop and release, 3) revise and ratify. Each phase includes 2-3 steps and associated actions that are supported by the Ocean Best Practices System ( www.oceanbestpractices.org ). The Australian case study differs from many other practices, which only use the second phase (develop and release). In this article, we emphasize the value of the other phases to ensure a practice is truly a ‘best practice’. These phases also have other benefits, including higher uptake of a practice stemming from a sense of shared ownership (from scope and recruit phase) and currency and accuracy (from revise and ratify phase). Although the process described in this paper may be challenging and time-consuming, it optimizes the chance to develop a true best practice that is a) fit-for-purpose with clearly defined scope; b) representative and inclusive of potential users; c) accurate and effective, reflecting emerging technologies and programs; and d) supported and adopted by users.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A Suite of Field Manuals for Marine Sampling to Monitor Australian Waters - Rachel Przeslawski; Scott Foster; Jacquomo Monk; Neville Barrett; Phil Bouchet; Andrew Carroll; Tim Langlois; Vanessa Lucieer; Joel Williams; Nicholas Bax (Frontiers in Marine Science, 2019)

Comparative performance evaluation of handpump water-supply technologies in northern Kenya and The Gambia - Tim Foster; Brian McSorley; Juliet Willetts (Hydrogeology Journal, 2019)

An assessment of bumblebee (Bombus spp) land use and floral preference in UK gardens and allotments cultivated for food - Gemma Foster; James Bennett; Tim Sparks (Urban Ecosystems, 2017)

Global impacts of the 1980s regime shift - Philip C. Reid; Renata E. Hari; Grégory Beaugrand; David M. Livingstone; Christoph Marty; Dietmar Straile; Jonathan Barichivich; Eric Goberville; Rita Adrian; Yasuyuki Aono; Ross Brown; James Foster; et al. (Global Change Biology, 2016)
Despite evidence from a number of Earth systems that abrupt temporal changes known as regime shifts are important, their nature, scale and mechanisms remain poorly documented and understood. Applying principal component analysis, change‐point analysis and a sequential t ‐test analysis of regime shifts to 72 time series, we confirm that the 1980s regime shift represented a major change in the Earth's biophysical systems from the upper atmosphere to the depths of the ocean and from the Arctic to the Antarctic, and occurred at slightly different times around the world. Using historical climate model simulations from the Coupled Model Intercomparison Project Phase 5 ( CMIP 5) and statistical modelling of historical temperatures, we then demonstrate that this event was triggered by rapid global warming from anthropogenic plus natural forcing, the latter associated with the recovery from the El Chichón volcanic eruption. The shift in temperature that occurred at this time is hypothesized as the main forcing for a cascade of abrupt environmental changes. Within the context of the last century or more, the 1980s event was unique in terms of its global scope and scale; our observed consequences imply that if unavoidable natural events such as major volcanic eruptions interact with anthropogenic warming unforeseen multiplier effects may occur.

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Reducing Risks to Rural Water Security in Africa - Rob Hope; Tim Foster; Patrick Thomson (Ambio, 2012)

An integrated lake-catchment approach for determining sediment source changes at Aqualate Mere, Central England - Nathan J. Pittam; Ian D. L. Foster; Tim M. Mighall (Journal of Paleolimnology, 2009)

Cultural, environmental and historical controls of vegetation patterns and the modern conservation setting on the island of Martha's Vineyard, USA - David R. Foster; Brian Hall; Sylvia Barry; Susan Clayden; Tim Parshall (Journal of Biogeography, 2002)
Aim Long‐term studies of landscape dynamics in relationship to changes in cultural, environmental and disturbance factors have great potential for increasing the understanding of modern ecological conditions and improving the development of conservation plans that incorporate historically important processes. In this study we compiled archaeological, historical, palaeoecological and ecological information on Martha's Vineyard to investigate temporal and spatial variation in landscape pattern and process. Although 2 , this island off the Massachusetts coast embraces remarkable geographical variation and harbours uncommon plant and animal assemblages that make it a national priority for conservation. Location The study embraces the entire island of Martha's Vineyard, which lies c. 8 km south of Cape Cod and the mainland of Massachusetts. The triangular‐shaped island contains three major geomorphological regions: moraine forms a series of irregular and subparallel ridges and hills 40 to over 80 m in elevation that terminate at the western end of the island in high cliffs at Gay Head and Squibnocket; sandy glacial outwash overlying moraine spreads down the northeastern end of the island forming a region of low undulating hills and shallow depressions 15–30 m in elevation, and an extensive outwash plain stretches across the central and eastern part of the island and slopes gently from 30‐m elevation in the north to 100 m of Quaternary and coastal plain sediments. Methods Long‐term records of vegetation, fire, natural disturbance and human activity were compiled over the past 2000 years and across the physiographic variation on the island. Palaeoecological interpretations of vegetation, fire, climate and land‐use history are based on a series of eleven stratigraphies from ponds, lakes and wetlands; archaeological data were compiled from recent surveys; historical data were assembled from census and town records, fire records, aerial photographs and cartographic series; and ecological information was derived from forestry and conservation surveys and field sampling of vegetation, soils and site characteristics. Extensive use was made of geographical information systems and multivariate statistical analyses. Results Spatial patterns in vegetation over the past 2000 years have varied strongly with soils and physiography, which are also associated with major differences in fire and land‐use history. Mesic hardwood forests that seldom burned occupy the western moraine, open oak‐pine and hardwood forests occur on the frequently burned and dissected outwash plain along the south coast, and pine‐oak forests cover the central outwash plain, which extends across much of the island and displays among the highest charcoal values in New England. Although a relatively large Native American population may have been an important source of fire ignitions there is no palynological or archaeological evidence that this culture cleared substantial areas or directly altered the extent of forest cover. Shifts in forest composition and fire were associated with regional climate change during the pre‐European period, whereas pronounced changes in forest cover and the development of extensive open‐land areas of grassland, shrubland and heathland were driven by European land use. The contrasting characteristics, land‐use histories and ownerships of different regions of the island yield contrasting conservation priorities and management directions. The mesic morainal forests have changed modestly in composition during the historical period and can effectively support a distinct woodland flora if adequately protected. The large outwash plain is broken by non‐native plantations but could yield an effective landscape mosaic of oak and pine forests interrupted by extensive scrub oak barrens that could be maintained through prescribed fire or cutting. In contrast, the south shore grasslands and shrublands are the product of intensive agricultural land use. These habitats and their unusual suite of plants and animals require traditional land‐use practices, or their substitutes, in order to reverse the ongoing increase in woody species and to maintain these cultural landscapes. Main Conclusion The biotic, edaphic, disturbance and historical diversity across this relatively small landscape is remarkable and yet poses many challenges to interpretation and conservation. The modern landscape can only be understood through knowledge of its long‐term past and can be best managed in the context of the natural and cultural factors that have shaped it through time.